THE FLIPPED-BROADCAST LEARNING SYSTEM, APPLICATION ON AZORES - Cabral, João; Nunes, Jerónimo (European Scientific Journal, ESJ, 2015)
On this work we suggest a teaching solution that can be implemented in Azores, an archipelago of nine islands of Portugal, based in already known system of e-learning, with a twist based on the flipped method. Structured in a cooperative way, the organization of the system allows to isolated groups of people to have access to a certain level of teaching, if they cannot have the possibility to have physical presence in school due to problems emerging from territory discontinuity. Our suggestion can be elaborate in a model that can be adapted to any level of education, and can be adapted also in cases that a cut of budget exists. We suggest the name of fb-learning: Flipped Broadcast Learning.